Preparation and characterization of activated CMK-1 with Zn and Ni species applied in hydrogen storage - Juárez, Juliana María; Gómez Costa, Marcos Bruno; Anunziata, Oscar Alfredo (Wiley Online Library, 2015)
The aim of this work is to prepare CMK-1 modified with Zn and Ni in order to improve its capacity in hydrogen stor- age. The approach that we have followed includes synthesis of nanostructures with the experimental study of its ad- sorption capacity and storage properties. We have shown that CMK-1 ordered porous carbon modified with metals is a promising material for hydrogen storage. The incorporation of metals was performed by wetness impregnation. The samples were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron micro- scope, transmission electron microscopy, X-ray photoelectron spectroscopy, and Brunauer–Emmett–Teller methods. The CMK 1 modified with Zn showed the highest H2 uptake at 77 K and at low and high pressure (1.5 and 4.4 wt.% at 1 and 10 bar, respectively). The introduction of Ni into CMK-1 does not increase hydrogen storage capacity at low pres- sure. However, at a higher pressure (10 bars), Ni-CMK-1 displays improved results in hydrogen uptake compared with those of CMK-1 pristine, 2.4 and 2.1 wt.%, respectively.. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: CMK-1; Zn-CMK-1; Ni-CMK-1; Hydrogen; Storage; Composite